A Study on the Performance Appraisal by Advinar Technology Pvt. Ltd. in Thiruvananthapuram District (Global Journal of Management and Business Research, 2022)
Performance appraisal has gradually more become part of a strategic approach to integrating HR activities and business policies and may now be seen as a general term covering a diversity of activities during which organizations request to assess employees and develop their capability, improve performance, and distribute rewards. A performance appraisal system embodies the tools and actions used by taught assessors in conducting the evaluation of employees. A random survey involving 200 human resource employees of the Advinar Technologies was carried out from January to July 2021. Participants from each Department were selected using simple random sampling (SRS) and the survey was supplemented by structured questionnaire adopted from literature reviews. The collected data was entered into SPSS Software version 20.0 and was cleaned and analyzed. Descriptive analyses of variance and Binary logistic regression and Cross tabulation with Chi-Square was used. The results were summarized as crude and adjusted odds ratios at 95% confidence intervals. The findings show that there was Impact of Performance Appraisal on Employee Productivity in Advinar Technologies Pvt. Ltd.